Effect Combination of Nitrogen Fertilizer Doses and Plant Growth Promoting Rhizobacteria (PGPR) Concentrations on Growth and Yield of Rice (Oryza sativa L.) Inpari 32 Variety - Marpaung, Winda M. R.; Maghfoer, Moch. Dawam; Karyawati, Anna Satyana (Universitas Panji Sakti, 2024)
The research was conducted to obtain the right combination of N fertilizer doses and PGPR concentrations for the growth and yield of Inpari 32 rice in Ampeldento Village, Karangploso District, Malang Regency, East Java, from May until September 2023. This used Randomized Block Design (RBD) consisted of 10 treatments, namely: P1(no fertilization), P2(50 kg.ha-1 N + 5 ml.l-1 PGPR), P3(50 kg.ha-1 N + 10 ml.l-1 PGPR), P4(50 kg.ha-1 N + 20 ml.l-1 PGPR), P5(100 kg.ha-1 N + 5 ml.l-1 PGPR), P6(100 kg.ha-1 N + 10 ml.l-1 PGPR), P7(100 kg.ha-1N + 20 ml.l-1 PGPR), P8(150 kg.ha-1 N + 5 ml.l-1 PGPR), P9(150 kg.ha-1 N + 10 ml.l-1 PGPR), and P10(150 kg.ha-1 N + 20 ml.l-1 PGPR), and repeated three times. The variables observed were plant height, number and area of leaves, number of tillers, dry weight of the plant, number of panicles, number of filled grains per clump, percentage of empty grain, number of milled dry grain, and grain yield per hectare. The experimental results showed that the treatment of 50 kg.ha-1 N + 5 ml.l-1 PGPR (P2) significantly affected the growth component and greater yield and yield component. In grain yields per hectare treatment of 50 kg.ha-1 N + 5 ml.l-1 PGPR (P2) gave significantly different result namely 8.03 tons ha-1, but not significantly different from other treatments.